Optimalisasi Produksi Alat Gali Muat dengan Metode Overall Equipment Effectiveness (OEE) pada Pada KegiatanOre Getting di PT. Bhakti Karya Mandiri Jobsite KM. 17, Kecamatan Toba, Kabupaten Sanggau – Kalimantan Barat - Jefri Julianda Putra; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. Based on data from bauxite production in April 2019 at PT. Bhakti Karya Mandiri, bauxiteproduction did not reach the target. the production target is 25000 bcm. but the production achieved wasonly 16,916 bcm. This is caused by wasted work time and disruption time which causes operating timeand productivity to be low. To determine the potential for improving the production process and theeffectiveness of using equipment, an analysis using the overall shipping effectiveness (OEE) methodneeds to be done. After analysis and improvement methods were carried out, the production of KobelcoSK 330 exceeded the planned target which was previously 16,916 bcm to 25,629 m³. But the OEE valueis still <61% not yet achieved the world class OEE> 85%, it can be concluded that the use of equipmentis not optimal. Better to make improvements to reduce wasted working hoursKeywords: Bauxite Mining, Overall Shipping Effectiveness (OEE) Method, Production, Excavator, and Dump Truck